2015
DOI: 10.1504/ijdsrm.2015.072770
|View full text |Cite
|
Sign up to set email alerts
|

Students' perceptions of service quality at a Greek higher education institute

Abstract: Competition in the higher education industry is becoming more and more intense. Higher education institutes need to focus their efforts on measuring service quality and develop processes for improving offered services in order to satisfy students, their primary customers, and other stakeholders. HEdPERF is a comprehensive performance-based measuring scale that captures the authentic determinants of service quality within the sector of higher education. However, when HEdPERF scale is used in different countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…Mansoor and Ali (2015) said in Sri Lankan universities that students' satisfaction on their academic performance quality was 3.29. However, the results are contradicting to Vrana et al (2015) who concluded that students' perception about service quality offered by Greece higher education institutes was less than expected. Ong and Casillano (2017) indicated that in Eastern Samar State University, the students' perception about the offered service quality was less than average.…”
Section: Results Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Mansoor and Ali (2015) said in Sri Lankan universities that students' satisfaction on their academic performance quality was 3.29. However, the results are contradicting to Vrana et al (2015) who concluded that students' perception about service quality offered by Greece higher education institutes was less than expected. Ong and Casillano (2017) indicated that in Eastern Samar State University, the students' perception about the offered service quality was less than average.…”
Section: Results Discussioncontrasting
confidence: 83%
“…There is a gap between students' expectations and perceptions related to reliability, tangibility, assurance, empathy and responsiveness in Malaysian private universities (Ansary et al, 2014). In higher education institutes in Greece, students' perception about service quality was less than expected, where facilities rated 5.10 out of seven, academic aspects 4.87, program 4.72, support services 4.57 and academic staff 4.26 (Vrana et al, 2015). In Sri Lankan universities, students' satisfaction on their academic performance quality was 3.29 out of five (Mansoor and Ali, 2015).…”
Section: Effect Of Service Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Quality services and undergraduate communication assist students in the decision-making process and will attract more students to choose university at the Technological Education Institute of Central Macedonia (TEICM) where students generally have positive opinions about the institution (Vrana, Dimitriadis, & Karavasilis , 2015). Inadequate research where student perceptions do not meet student expectations for overall service quality at certain Higher Education in South Africa (Martinez-Arguelles & Batalla-Busquet, 2016).…”
Section: Service Quality (Servqual)mentioning
confidence: 99%